Penerapan Metode Constraint Programming Pada Penjadwalan Mata Pelajaran di MTs Khaulafaur Rasyidin - Basuki Ilham, Maulana; Ikhwan Ruslianto; Hidayati, Rahmi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Scheduling subjects is a component found in educational institutions. In the creation of school subject schedules, it is not only the school subjects that must be considered; The availability of teachers, the classes, and the appropriate time slots must all be taken into account to prevent conflicting schedules. To address scheduling issues, a high level of precision is required, especially when schedules are created manually. Based on these issues, a system is needed to accurately solve problems, ensuring that no scheduling conflicts occur. This school subject scheduling system is built at MTs. Khaulafaur Rasyidin. The system built is a web-based scheduling application using constraint programming. The number of scheduling slots used from Monday to Saturday is 7 slots, with only 6 slots available on Fridays. Each class is scheduled for learning activities for 6 days per week from Monday to Saturday. Therefore, each class has 41 scheduling slots per week. Testing is conducted five times to assess the accuracy of the system. The five tests involve the system processing the scheduling using five different types of soft constraints. After conducting these five tests, the system successfully resolves scheduling issues with 164 slots without generating conflicting schedules, with an average accuracy of the system against all constraints of 85.81%